Biofilm Based on Modified Sago Starch: Preparation and Characterization - Dewi Sondari; Faizatul Falah; Riska Suryaningrum; Fahriya Puspita Sari; Athanasia Amanda Septefani; Witta Kartika Restu; Yulianti Sampora (Dept. of Chemical Engineering, Diponegoro University, 2019)
Biofilms made from modified sago starch to improve the mechanical and physical properties have been studied. This study aimed to prepare and characterize biofilms from sago starch and modified sago (acetylation, oxidation, cross-link and precipitation). Modified of sago starch was prepared by some methods: precipitation using ethanol as solvent, acetylation modified of sago starch using acetic anhydride, oxidation modification using hydrogen peroxide and cross-link modification using sodium acetate. Biofilms were made from modified sago using glycerol with a concentration of 1.0% weight, where glycerol acts as a plasticizer to impart the thermoplasticity of the starch film. Biofilm made from native sago was then compared to biofilm from modified sago starch. The effects of modified sago starch to the biofilm were measured on its moisture contents, contact angle value, mechanical properties such as elongation and tensile strength. The chemical structures were evaluated by Fourier-transform infrared spectroscopy (FTIR) and morphology of biofilm were measured by Scanning Electron Microscope (SEM). The optimum condition of modified sago starch used in biofilm in this study is by acetylation. The result show that modified acetylation of sago starch can improve the properties of biofilm Keywords: biofilms, sago, acetylation, oxidation, cross link, SEM, FTIR